ANALISIS RISIKO LONGSOR DI KECAMATAN KELING, KABUPATEN JEPARA - Hamida, Fakhryza Nabila; Widyasamratri, Hasti; Poedjiastoeti, Hermin (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2024)
Keling District, Jepara Regency conducted a landslide risk analysis to determine the area's susceptibility and develop workable mitigation solutions. The analytical procedure includes threat identification, vulnerability and capacity evaluation, and methodology-based risk determination. The data used were topography, soil and rock types, joints and faults, rainfall, land use, and the frequency of disasters. Landslide-prone areas were mapped, and contributing factors were evaluated through the application of the VCA (Vulnerability Capacity Analysis) matrix multiplication approach. The findings demonstrate that population growth, deforestation, clearance of additional land, excessive rainfall, erosion-prone soil and rock conditions, and uncontrolled human activities contribute to the likelihood of landslides in Keling District. Building landslide infrastructure, raising public awareness, and closely monitoring changes in land use are all advised mitigating techniques. This strategy's implementation is anticipated to lower the likelihood of landslides and improve readiness for potential natural disasters.